Management of blunt force bladder injuries: A practice management guideline from the Eastern Association for the Surgery of Trauma. Issue 2 (February 2019) - Yeung, Lawrence L.; McDonald, Amy A.; Como, John J.; Robinson, Bryce; Knight, Jennifer; Person, Michael A.; Lee, Jane K.; Dahm, Philipp
Abstract : BACKGROUND: The diagnostic evaluation and clinical management of bladder injuries caused by blunt force trauma are variable. We aim to formulate a practice management guideline using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. METHODS: The working group, patient, intervention, comparator, outcome (PICO), formulated four questions regarding the following topics: (1) diagnostic evaluation based on patient baseline risk of bladder injury (computed tomography cystography vs. no imaging); (2) management of intraperitoneal bladder injuries (operative versus nonoperative); (3) management of extraperitoneal bladder injuries based on complexity of injury (operative vs. nonoperative); and (4) diagnostic follow-up of bladder injuries based on complexity of repair (cystography vs. no cystography). A systematic review of the MEDLINE database for English language articles with adult patients was undertaken. RevMan 5 (Review Manager (RevMan) [Computer program]. Version 5.3. Copenhagen: The Nordic Cochrane Centre, The Cochrane Collaboration, 2014) and GRADEpro (GRADEpro GDT: GRADEpro Guideline Development Tool [Software]. McMaster University, 2015) software were used. Recommendations were voted on by working group members. Consensus was obtained for each recommendation. RESULTS: Three hundred ninety-three articles were screened, resulting in a full-text review of 64 articles. Seventeen articles were used to formulate the recommendations of this guideline. Several recommendations are made. The need for initial computed tomography cystography after trauma depends on characteristics of the trauma itself, but it is not recommended in patients without gross hematuria. In general, patients with intraperitoneal bladder ruptures should undergo operative repair. This is not routinely necessary in those with extraperitoneal ruptures unless the injury is complex. The need for follow-up cystography after bladder repair depends on the risk of urine leak. Those with low risk of urine leak do not require a follow-up study. CONCLUSION: Using the GRADE process, the panel made nine recommendations based on four PICO questions concerning the evaluation and management of blunt force bladder injuries. Abstract : Supplemental digital content is available in the text.